Question-led approach in designing Dijkstra algorithm game-based learning: A pilot study - Rosni Binti Ramle; D’oria Islamiah Rosli; Shelena Soosay Nathan; Mazniha Berahim (International Journal of Evaluation and Research in Education (IJERE), 2020)
Dijkstra algorithm is important to be understood because of its many uses. However, understanding it is challenging. Various methods to teach and learn had been researched, with mixed results. The study proposes questionled approach of the algorithm in a game-based learning context. The game designed based on an existing game model, developed and tested by students. Pre- and post-game tests compared and game feedback survey analysed. Results showed that students’ performance in graph data structure Dijkstra algorithm improved after playing the game where post-test mark was higher than pre-test. Game feedback were mostly positive, with areas of improvement. Students may use the game as a learning tool for self-regulated learning. Educators may get some ideas on how to design teaching tool using question-led approach.